2020
DOI: 10.3389/fmicb.2020.01527
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Discloses the Uniqueness and the Biosynthetic Potential of the Marine Cyanobacterium Hyella patelloides

Abstract: Baeocytous cyanobacteria (Pleurocapsales/Subsection II) can thrive in a wide range of habitats on Earth but, compared to other cyanobacterial lineages, they remain poorly studied at genomic level. In this study, we sequenced the first genome from a member of the Hyella genus-H. patelloides LEGE 07179, a recently described species isolated from the Portuguese foreshore. This genome is the largest of the thirteen baeocyteforming cyanobacterial genomes sequenced so far, and diverges from the most closely related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
(86 reference statements)
3
11
0
Order By: Relevance
“…The genome of H. disjuncta PCC 6712 was sequenced and published by Shih et al 2013 [ 15 ] and a comparison with H. patelloides LEGE 07179 (as reference genome) was performed by Brito et al 2020 [ 14 ]. Here, we have expanded the genomic analysis of H. disjuncta PCC 6712 to include genes involved in multicellularity, nitrogen fixation, the presence of encoded BGCs (AntiSMASH) and potential antibiotic resistance mechanisms (ARTS 2.0).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The genome of H. disjuncta PCC 6712 was sequenced and published by Shih et al 2013 [ 15 ] and a comparison with H. patelloides LEGE 07179 (as reference genome) was performed by Brito et al 2020 [ 14 ]. Here, we have expanded the genomic analysis of H. disjuncta PCC 6712 to include genes involved in multicellularity, nitrogen fixation, the presence of encoded BGCs (AntiSMASH) and potential antibiotic resistance mechanisms (ARTS 2.0).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the H. disjuncta PCC 6712 within the AntiSMASH framework was used to identify BGCs that may be present in other cyanobacterial genomes or are likely to be species/strain specific. Interestingly, none of the cryptic BGCs were present in H. patelloides LEGE 07179 as a result of the AntiSMASH search, although Brito et al 2020 [ 14 ] found similarities in gene cluster families between the two organisms when using BiG-SCAPE analysis with a 0.7 cut-off which included a single terpene BGC (Region 3.11) and the NRPS-like gene cluster corresponding to the known 1-heptadecene pathway (Region 3.9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations